2014
DOI: 10.1038/cr.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of biclonal origin and a novel oncogene SLC12A5 in colon cancer by single-cell sequencing

Abstract: Single-cell sequencing is a powerful tool for delineating clonal relationship and identifying key driver genes for personalized cancer management. Here we performed single-cell sequencing analysis of a case of colon cancer. Population genetics analyses identified two independent clones in tumor cell population. The major tumor clone harbored APC and TP53 mutations as early oncogenic events, whereas the minor clone contained preponderant CDC27 and PABPC1 mutations. The absence of APC and TP53 mutations in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 24 publications
(31 reference statements)
2
100
0
1
Order By: Relevance
“…In recent years, a large number of studies have been reported using single cell analysis to analyze individual tumor cells isolated from breast cancer (Navin et al, 2011; Deng et al, 2014; Wang et al, 2014; Eirew et al, 2015), colon cancer (Zong et al, 2012; Yu et al, 2014), pancreatic adenocarcinomas (Ruiz et al, 2011), muscle-invasive bladder cancer (Li et al, 2012b), intestinal cancer (Grün et al, 2015), lung adenocarcinoma cancer (Kim et al, 2015), renal cell carcinoma (Gerlinger et al, 2012; Li et al, 2012b), and acute myeloid leukemia (Ding et al, 2012; Hughes et al, 2014; Paguirigan et al, 2015). For example, Navin and colleagues investigated copy number variation in single tumor cells using DOP WGA followed by DNA sequencing to determine cell population structure and tumor evolution patterns in a single breast tumor (Navin et al, 2011).…”
Section: Application Of Single Cell Analysismentioning
confidence: 99%
“…In recent years, a large number of studies have been reported using single cell analysis to analyze individual tumor cells isolated from breast cancer (Navin et al, 2011; Deng et al, 2014; Wang et al, 2014; Eirew et al, 2015), colon cancer (Zong et al, 2012; Yu et al, 2014), pancreatic adenocarcinomas (Ruiz et al, 2011), muscle-invasive bladder cancer (Li et al, 2012b), intestinal cancer (Grün et al, 2015), lung adenocarcinoma cancer (Kim et al, 2015), renal cell carcinoma (Gerlinger et al, 2012; Li et al, 2012b), and acute myeloid leukemia (Ding et al, 2012; Hughes et al, 2014; Paguirigan et al, 2015). For example, Navin and colleagues investigated copy number variation in single tumor cells using DOP WGA followed by DNA sequencing to determine cell population structure and tumor evolution patterns in a single breast tumor (Navin et al, 2011).…”
Section: Application Of Single Cell Analysismentioning
confidence: 99%
“…In gastric cancer cases, PABPC1 has been found to be an oncoprotein 62 and observed to exert carcinogenesis. In colon cancer mutations in PABPC1 have been found in minor tumor clones 63 . Genomic correlates of immune-cell infiltrates in CRC have found the existence of significantly mutated CRC genes 64 .…”
Section: Dicationmentioning
confidence: 99%
“…Recently, a series of exciting studies utilizing SCS in some major cancers were reported, such as breast cancer (16,47), colon cancer (18,67), muscle-invasive bladder cancer (68), intestinal cancer (69), lung adenocarcinoma cancer (27), kidney tumor (70), and acute myeloid leukemia (71,72). These studies made unprecedented progress in understanding carcinogenesis, progression, metastasis, and drug resistance.…”
Section: Preliminary Applications Have Led To Exciting Discoveriesmentioning
confidence: 99%
“…Interestingly, some genes discovered by SCS exhibited a high frequency of mutations at the single-cell level, but low prevalence in the tumor mass (16,67). Some genes exhibited specific alternative splicing of exon isoforms in different single-cell transcriptomes (30).…”
Section: Preliminary Applications Have Led To Exciting Discoveriesmentioning
confidence: 99%